Comparative study of Mirs’(Mushtaq and Shabir) technique of prepuce preserving minimally invasive urethroplasty with Snodgrass urethroplasty for repair of distal hypospadias without chordee…A prospective study - Mushtaq Mir; Shabir Ahmad Mir; Muddassir Shahdhar; Mumtazdin Wani; Hakim Adil Moheen; Jahangeer Ahmad Bhat (Indian Journal of Plastic Surgery)
Background: There is no single, universally applicable technique for hypospadias repair and numerous techniques have been practised from time to time. We compare the results of our new technique (Mirs’ technique also called Mush & Shab’s technique) to Snodgross urethroplasty. Mirs’ technique is a modified version of Thiersch-Duplay urethroplasty. Material and Methods: This prospective comparative study was carried out in a tertiary care hospital of Northern India over a period of 3 years from March 2010 to March 2013 and included 120 patients of anterior (distal penile, subcoronal, coronal and glanular) hypospadias without chordee. They underwent either Mirs’ technique (group 1 n = 60) or Snodgrass technique (group 2 n = 60). Follow-up was at 1-week, 1-month, 3 months and 6 months. Results: The mean operative time was 55 min (range: 43-70 min) in group 1 and 71.9 min (range: 60-81 min) in group 2 (P & 0.001). Urethrocutaneous fistula developed in two and four patients in group 1 and 2, respectively. Fistula closure was done at least 3 months postoperatively, and there was no significant difference in success rate between the two groups. Three cases of glanular dehiscence were detected (one in group 1 and two in group 2); the patient from group 1 had a successful repair using the already preserved prepuce. Conclusion: Mirs’ modification of Thiersch-Duplay technique for distal hypospadias is a time saving procedure with a lower overall complication rate. Valuable local tissue is preserved to deal with any complication that may occur. Analgesic requirement was significantly lower in this minimally traumatic technique. As it is less time consuming, simple and easy to learn with a short learning curve, this technique deserves application in cases of distal hypospadias.